Linguistic stereotypes in the Nigerian banking industry (2017)
Stereotypes are generalizations or assumptions that people make about the characteristics of all members of a group, based on an image (often wrong) about what people in that group are like. The concept has received some scholarly attention. However, it has not been extended to cover linguistic stereotypes, occasioned by the influx of technological devices that are used to communicate with customers in the banks. This is exactly what engages our attention in this paper. Paul Grice's 'Cooperative Principle', which states that: The success of every conversation depends not only on what speakers say, but on their whole approach to the interaction was adopted in this study. Ten statements repeatedly used by the security doors at the entrance of the banks, the Automated Teller Machine (ATM) and bank personnel’s are purposively selected for analysis in this research. Findings reveal that these statements are extremely repetitive, and monolithic, grossly in appropriate in some situations and lack the flexibility and accuracy of human use of language. These features are contradictory to the natural attributes of language which are dynamism and appropriateness to different communicative situations. Linguistic skills entail more than the mastery of a linguistic code that allows the language user to produce sentences that are grammatical. They also involve knowing how to use language in different social settings. That is, knowing what to say, to whom and how to say it appropriately in any given situation. These attributes are seriously compromised when engines are made to talk like men. However, the researcher is of the view that if these statements are modified as recommended in the paper, they would still be appropriate